A promising self-nanoemulsifying adjuvant with plant-derived saponin D boosts immune response and exerts an anti-tumor effect - Luo, Xing; Song, Zhen; Zeng, Xiaogqiang; Ye, Yan; Zheng, Hailin; Cai, Dingyi; Yuan, Qingpeng; Li, Haibo; Tong, Yanan; Lu, Dongshui; Liu, Yuheng; Zeng, Hao; et al. (Frontiers in Immunology, 2023)
Objectives The low immunogenicity of tumor antigens and unacceptable toxicity of adjuvants has hindered the application and development of tumor vaccines. Hence, we designed a novel anti-tumor vaccine composed of a plant-derived immunostimulant molecular nanoadjuvant (a self-nanoemulsifying system, SND) and the antigen OVA, to reinvigorate the immune response and inhibit tumor progression. Methods In this study, this novel nanoadjuvant with Saponin D (SND) was designed and prepared by low-energy emulsification methods. Several important characteristics of the SND, including morphology, size, polymer dispersity index (PDI), zeta potential, and stability, were estimated, and the cytotoxicity of the SND was evaluated by MTT assay. Additionally, the immune response in terms of antibody titer levels and cellular immunity were evaluated in vivo after immunization with the vaccine, and the preventative and therapeutic effects of this novel vaccine against tumors were estimated. Finally, the antigen release profile was determined by IVIS imaging and by in vivo assay. Results This SND nanoadjuvant had good characteristics including the average particle size of 26.35 ± 0.225 nm, narrow distribution of 0.221 ± 1.76, and stability zeta potential of -12.9 ± 0.83 mV. And also, it had good stability (size, PDI, zeta potential, antigen stability) and low toxicity in vitro and in vivo, and delayed antigen release in vivo. The humoral immune response (IgG, IgG1, IgG2a, and IgG2b) and cellular immune level (cytokines of splenocytes including IFN-γ, IL-4, IL-1β andIL-17A) were both improved greatly after injected immunization at 0, 14, 28 days with the novel nanoadjuvant and antigen OVA. Importantly, this novel nanoadjuvant combined with OVA might lead to the induction of the prevent and treatment efficacy in the E.G7-OVA tumor-bearing mice. Conclusions These results suggested that this novel nanoadjuvant encapsulated natural plant immunostimulant molecular OPD could be a good candidate of tumor vaccine adjuvant for reinvigorating the immune response and powerfully inhibiting tumor growth effect.